2012
DOI: 10.1186/1471-213x-12-30
|View full text |Cite
|
Sign up to set email alerts
|

3D-FISH analysis of embryonic nuclei in mouse highlights several abrupt changes of nuclear organization during preimplantation development

Abstract: BackgroundEmbryonic development proceeds through finely tuned reprogramming of the parental genomes to form a totipotent embryo. Cells within this embryo will then differentiate and give rise to all the tissues of a new individual. Early embryonic development thus offers a particularly interesting system in which to analyze functional nuclear organization. When the organization of higher-order chromatin structures, such as pericentromeric heterochromatin, was first analyzed in mouse embryos, specific nuclear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 64 publications
8
77
0
Order By: Relevance
“…In the maternal pronucleus, the pericentromeres occupy the surface of the NPB already from a few hours after pronuclear formation. In contrast, the pericentromeric repeats in the male pronucleus first cluster in an unorganized mass at the center of the pronucleus and restructure around the surface of the NPBs later compared with the maternal pronucleus (Aguirre-Lavin et al 2012). The chromatin structure of mature sperm provides a plausible explanation for this asymmetry, as pericentromeric domains are found in a single cluster in the center of the sperm nucleus (Haaf and Ward 1995).…”
Section: Chromatin Organization Of the Preimplantation Embryomentioning
confidence: 77%
See 1 more Smart Citation
“…In the maternal pronucleus, the pericentromeres occupy the surface of the NPB already from a few hours after pronuclear formation. In contrast, the pericentromeric repeats in the male pronucleus first cluster in an unorganized mass at the center of the pronucleus and restructure around the surface of the NPBs later compared with the maternal pronucleus (Aguirre-Lavin et al 2012). The chromatin structure of mature sperm provides a plausible explanation for this asymmetry, as pericentromeric domains are found in a single cluster in the center of the sperm nucleus (Haaf and Ward 1995).…”
Section: Chromatin Organization Of the Preimplantation Embryomentioning
confidence: 77%
“…Recently, rRNA transcription has been detected at the NPB as early as the zygote (Lin et al 2014), contrary to previous data (Zatsepina et al 2003), which suggested that rDNA transcription commences only at the late two-cell stage. The number of NPBs decreases during the cell cycle and over the progression from the zygote to the eight-cell stage, and the conventional tripartite morphology of somatic-type nucleoli gradually starts to appear forming around the NPB as a core (Flechon and Kopecny 1998;Aguirre-Lavin et al 2012). Importantly, within 3 h after SCNT, NPBs morphologically identical to those in fertilized embryos form, and their number correlates with developmental potential, raising the possibility that NPB formation might be a critical component of reprogramming to the totipotent state (Martin et al 2006b).…”
Section: Nucleolar Precursor Bodies (Npbs) Are Major Organizers Of Emmentioning
confidence: 99%
“…The time-course of nuclear remodeling events differed during the first blastomere cleavage events, but IVF and cloned embryos achieved the same distinct nuclear organization in the majority of embryos at the 8-cell stage. Aguirre-Lavin et al 5 combined 3D-FISH, 3D-CLSM and quantitative 3D image analyses to study nuclear arrangements of centromeric (minor satellites), pericentromeric (major satellites), and telomeric genomic sequences, as well as nucleolar precursor bodies and nucleoli in naturally fertilized mouse embryos from the zygote to blastocyst stage. Remarkable changes of nucleolar precursor bodies and pericentromeric heterochromatin were noted during the transition from the mouse 2-cell to the 4-cell stage.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,10 For this purpose, one has to take into account that mammalian species differ in the timing of major embryonic gene activation. 2 In rabbit embryos this event apparently starts, like in bovine embryos, at the 8-cell stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation